Low Apgar Score and Risk of Neonatal Mortality among Infants with Birth Defects - Ludorf, Katherine L.; Benjamin, Renata H.; Canfield, Mark; Shumate, Charles; Findley, Tina O.; Johnson, Anthony; Tsao, KuoJen; Agopian, A.J. (American Journal of Perinatology, 2024)
The Apgar score is a clinical tool to assess newborn health at delivery and has shown utility in predicting neonatal mortality in the general population, but its predictive ability in neonates with birth defects remains unexplored. As such, we aimed to investigate the performance of the 5-minute Apgar score in predicting neonatal mortality among neonates with a spectrum of major birth defects.Data for neonates with birth defects born between 1999 and 2017 were obtained from the Texas Birth Defect Registry. We generated receiver operating characteristic curves and corresponding area under the curve (AUC) values for neonatal mortality (death within the first 28 days of life) by 5-minute Apgar score (<7 vs. ≥7) to measure discrimination capacity. We performed secondary analyses to determine the predictive ability of the Apgar score: (1) among infants with an isolated birth defect and (2) separately in preterm and term neonates.Low Apgar score yielded substantial predictive ability for neonatal mortality, with 25 out of 26 AUC values > 0.70 across a spectrum of defect categories. High predictive ability was consistent among neonates with isolated defects, and preterm and term neonates.The Apgar score is likely useful for predicting neonatal mortality among most neonates with birth defects. Despite small sample sizes limiting some secondary analyses, the findings emphasize the potential continued use of the Apgar score as a rapid clinical assessment tool for newborns with birth defects. Continued research may refine the Apgar score's application in this important population, both in clinical practice and population health research.
Keywords: birth defects; Apgar score; neonates; neonatal mortality; prediction model